Analisis Faktor-Faktor dengan Kejadian Speech Delay pada Anak Pra Sekolah di PAUD As-Syafi’iyah Bicorong Pakong Pamekasan - Lianita Primi Octaviana; Nova Purmahardini; Nurvy Alief Aidillah (2023)
Optimal child growth and development is the expectation of every parent. The toddler period becomes a priority for the development of children's language skills which takes place very quickly and becomes the basis for further development. There are many factors that cause speech delay in children. One of them is the habit of children with gadgets, gender and type of childbirth. This study used an Analytical design with a Cross Sectional approach. The population used is all children in PAUD As-syafi'iyah Bicorong Pakong Pamekasan totaling 32 children. The sampling used is Total Sampling, which is all 32 children. The results showed that gender p value 0.003